Immunopathogenesis and immunotherapy of Culicoides hypersensitivity in horses: an update. Issue 6 (18th November 2021) - Marti, Eliane; Novotny, Ella N.; Cvitas, Iva; Ziegler, Anja; Wilson, A. Douglas; Torsteinsdottir, Sigurbjörg; Fettelschoss‐Gabriel, Antonia; Jonsdottir, Sigridur
Abstract : Culicoides hypersensitivity (CH) is a strongly pruritic dermatitis of horses, characterised histologically by mixed perivascular to diffuse cellular infiltrates of mononuclear cells and eosinophils, and caused by helper T cell (Th)2, immunoglobulin (Ig)E‐mediated reactions to antigens present in the saliva of biting Culicoides midges. As treatment of CH is still not satisfactory, a better knowledge of the pathogenesis of CH is needed for the development of new therapeutic modalities. Accordingly, availability of pure Culicoides allergens instead of crude whole body extracts is essential for the improvement of in vitro diagnosis of CH and development of a more effective allergen immunotherapy (AIT). Beside the Th2 cytokines interleukin (IL)‐4 and IL‐13, recent studies have shown the involvement of thymic stromal lymphopoietin, IL‐5 and IL‐31 in the pathogenesis of CH. The importance of IL‐5 and IL‐31 has been confirmed through targeting these cytokines by active immunisation of CH patients, resulting in a significant decrease of CH lesion scores. Thirty Culicoides salivary allergens have been described over the last 10 years and produced as pure recombinant (r‐) proteins. Use of a protein microarray has allowed the identification of the most relevant Culicoides r‐allergens for CH in central and northern Europe. An immunisation protocol has been developed for preventive AIT against CH. Small amounts of r‐ Culicoides allergens injected into the submandibular lymph nodes with Alum/MPLA as adjuvants seem to induce a suitable immune response for both preventive and therapeutic AIT. The next years will reveal whether these recent advancements will translate into an improved diagnosis, treatment and prevention of CH. Abstract : Culicoides hypersensitivity (CH) is a strongly pruritic dermatitis of horses, characterised histologically by mixed perivascular to diffuse cellular infiltrates of mononuclear cells and eosinophils, and caused by helper T cell (Th)2, immunoglobulin (Ig)E‐mediated reactions to antigens present in the saliva of biting Culicoides midges. As treatment of CH is still not satisfactory, a better knowledge of the pathogenesis of CH is needed for the development of new therapeutic modalities. Accordingly, availability of pure Culicoides allergens instead of crude whole body extracts is essential for the improvement of in vitro diagnosis of CH and development of a more effective allergen immunotherapy (AIT). Beside the Th2 cytokines interleukin (IL)‐4 and IL‐13, recent studies have shown the involvement of thymic stromal lymphopoietin, IL‐5 and IL‐31 in the pathogenesis of CH. The importance of IL‐5 and IL‐31 has been confirmed through targeting these cytokines by active immunisation of CH patients, resulting in a significant decrease of CH lesion scores. Thirty Culicoides salivary allergens have been described over the last 10 years and produced as pure recombinant (r‐) proteins. Use of a protein microarray has allowed the identification of the most relevant Culicoides r‐allergens for CH in central and northern Europe. An immunisation protocol has been developed for preventive AIT against CH. Small amounts of r‐ Culicoides allergens injected into the submandibular lymph nodes with Alum/MPLA as adjuvants seem to induce a suitable immune response for both preventive and therapeutic AIT. The next years will reveal whether these recent advancements will translate into an improved diagnosis, treatment and prevention of CH. Resumo: A hipersensibilidade a culicóides (HC) é uma dermatopatia fortemente pruriginosa de cavalos, caracterizada histologicamente por infiltrados de células mononucleares e eosinófilos perivasculares perivascular a difuso misto, e causada por células T helper (Th) 2, reações mediadas por imunoglobulina (Ig)E aos antígenos presentes na saliva de picadas de mosquitos Culicoides . Como o tratamento da HC ainda não é satisfatório, um melhor conhecimento da patogênese da HC é necessário para o desenvolvimento de novas modalidades terapêuticas. Conseqüentemente, a disponibilidade de alérgenos puros de Culicoides em vez de extratos brutos de corpo inteiro é essencial para a melhoria do diagnóstico in vitro de CH e o desenvolvimento de uma imunoterapia com alérgeno (IA mais eficaz. Além das citocinas Th2 interleucina (IL)‐4 e IL‐13, estudos recentes têm mostrado o envolvimento da linfopoietina estromal tímica, IL‐5 e IL‐31 na patogênese da HC. A importância de IL‐5 e IL‐31 foi confirmada através da neutralização dessas citocinas por imunização ativa de pacientes com HC, resultando em uma diminuição significativa dos escores de lesão de HC. Trinta alérgenos salivares de Culicoides foram descritos nos últimos 10 anos e produzidos como proteínas recombinantes (r‐) puras. O uso de um microarranjo de proteínas permitiu a identificação dos r‐alérgenos de Culicoides mais relevantes para o HC no centro e norte da Europa. Um protocolo de imunização foi desenvolvido para AI preventiva contra HC. Pequenas quantidades de r‐alérgenos de Culicoides injetados nos linfonodos submandibulares com Alum/MPLA como adjuvantes parecem induzir uma resposta imune adequada para AI preventiva e terapêutica. Os próximos anos revelarão se esses avanços recentes se traduzirão em um melhor diagnóstico, tratamento e prevenção da HC. 摘要: 库蠓超敏反应(CH)是马的一种严重瘙痒性皮炎, 由库蠓叮咬的唾液抗原引起, 辅助性T细胞(Th)2、免疫球蛋白(Ig)E介导的反应, 组织学特征为混合血管周围至弥漫性单核细胞和嗜酸性粒细胞浸润。由于CH的治疗仍不令人满意, 开发新的治疗方式首先要更好地了解CH的发病机制。因此, 用现有的纯库蠓过敏原代替全身粗提物, 对于改善CH的体外诊断, 以及开发更有效的过敏原免疫治疗(AIT)至关重要。 除了Th2细胞因子白细胞介素(IL)‐4和IL‐13外, 最近的研究表明胸腺基质淋巴细胞生成素、IL‐5和IL‐31参与了CH的发病机制。通过CH病患的主动免疫作用标靶这些细胞因子, 导致CH病变评分显著降低, 证实了IL‐5和IL‐31的重要性。在过去的10年中, 已经描述了30种库蠓唾液过敏原, 并作为纯重组(r‐)蛋白生产。使用蛋白质微阵列可以鉴定中欧和北欧CH最相关的库蠓r‐过敏原。已经开发了针对CH的预防性AIT的免疫方案。少量r‐库蠓过敏原以明矾/MPLA作为佐剂注射到颌下淋巴结, 这样的AIT似乎可预防性和治疗性诱导出有意义的免疫应答。 未来几年将揭示这些最新进展是否会转化为CH的改善诊断、治疗和预防。 Résumé: L'hypersensibilité aux culicoïdes (CH) est une dermatite fortement prurigineuse des chevaux, caractérisée histologiquement par des infiltrats cellulaires mixtes périvasculaires à diffus de cellules mononucléées et d'éosinophiles, et causée par des réactions médiées par les lymphocytes T auxiliaires (Th)2, les immunoglobulines (Ig)E aux antigènes présents dans la salive des moucherons piqueurs Culicoides . Le traitement de l'HC n'étant toujours pas satisfaisant, une meilleure connaissance de la pathogénie de l'HC est nécessaire pour le développement de nouvelles modalités thérapeutiques. En conséquence, la disponibilité d'allergènes Culicoides purs au lieu d'extraits bruts de corps entier est essentielle pour l'amélioration du diagnostic in vitro de l'HC et le développement d'une immunothérapie allergénique (AIT) plus efficace. Outre les cytokines Th2, interleukine (IL)‐4 et IL‐13, des études récentes ont montré l'implication de la lymphopoïétine stromale thymique, de l'IL‐5 et de l'IL‐31 dans la pathogénie de l'HC. L'importance de l'IL‐5 et de l'IL‐31 a été confirmée en ciblant ces cytokines par immunisation active des patients CH, entraînant une diminution significative des scores de lésions CH. Trente allergènes salivaires de Culicoides ont été décrits au cours des 10 dernières années et produits sous forme de protéines recombinantes pures (r‐). L'utilisation d'une puce à protéines a permis d'identifier les allergènes Culicoides r les plus pertinents pour la CH en Europe centrale et septentrionale. Un protocole d'immunisation a été développé pour l'AIT préventive contre CH. De petites quantités d'allergènes r‐ Culicoides injectées dans les ganglions lymphatiques sous‐maxillaires avec de l'alun/MPLA comme adjuvants semblent induire une réponse immunitaire appropriée pour l'AIT à la fois préventive et thérapeutique. Les prochaines années révéleront si ces progrès récents se traduiront par une amélioration du diagnostic, du traitement et de la prévention de l'HC. Zusammenfassung: Die Culicoides Hypersensibilität (CH) ist eine hochgradig juckende Dermatitis des Pferdes, die histologisch durch diffuse zelluläre Infiltrate von mononukleären Zellen und Eosinophilen charakterisiert ist, und durch T Helferzellen (Th) 2 und Immunglobulin (Ig) E‐mediierte Reaktionen auf Antigene, die im Speichel der beißenden Culicoides Mücken vorkommen, verursacht wird. Da die Behandlung von CH immer noch nicht zufriedenstellend verläuft, ist ein besseres Verständnis der Pathogenese der CH zur Entwicklung neuer Behandlungsmodalitäten, nötig. Ebenso ist die Verfügbarkeit von reinem Culicoides Allergen anstatt rohem Ganzkörperextrakt nötig, um die in vitro Diagnose von CH zu verbessern und eine effektivere Allergen Immuntherapie (AIT) entwickeln zu können. Neben den Th2 Zytokinen Interleukin (IL)‐4 und IL‐13 haben jüngste Studien eine Beteiligung von Thymic Stromal Lymphopoietin, IL‐5 und IL‐31 bei der Pathogenese von CH gezeigt. Die Bedeutung von IL‐5 und IL‐31 konnte bestätigt werden, indem auf diese Zytokine mittels aktiver Immunisierung bei CH Patienten abgezielt wurde, was zu einer signifikanten Abnahme der CH Läsionswerte führte. Im Verlauf der letzten 10 Jahre wurden dreißig Culicoides Speichelallergene beschrieben und als reine rekombinante (r‐) Proteine produziert. Der Einsatz eines Protein Mikroarrays hat eine Identifizierung der wichtigsten Culicoides r‐Allergene bei CH in Zentral‐ und Nordeuropa ermöglicht. Es wurde ein Immunisierungsprotokoll für eine präventive AIT gegen CH entwickelt. Kleine Mengen an r‐Culicoides Allergenen wurden dabei in den submandibulären Lymphknoten mit Alum/MPLA als Adjuvans injiziert, was eine geeignete Immunantwort sowohl für eine präventive wie auch eine therapeutische AIT induzierte. Die nächsten Jahre werden zeigen, ob diese jüngsten Fortschritte zu einer verbesserten Diagnose, Behandlung und Prävention von CH führen werden. Resumen: La hipersensibilidad a Culicoides (CH) es una dermatitis intensamente pruriginosa en caballos, caracterizada histológicamente por infiltrados celulares mixtos de perivasculares a difusos de células mononucleares y eosinófilos, y causada por células T colaboradoras (Th)2, reacciones mediadas por inmunoglobulina (Ig)E a los antígenos presentes en la saliva de los mosquitos Culicoides. Dado que el tratamiento de la CH aún no es satisfactorio, se necesita un mejor conocimiento de la patogénesis de l la CH para desarrollar nuevas modalidades terapéuticas. En consecuencia, la disponibilidad de alérgenos de Culicoides puros en lugar de extractos crudos de cuerpo entero es esencial para la mejora del diagnóstico in vitro de CH y el desarrollo de una inmunoterapia con alérgenos (AIT) más eficaz. Además de las citoquinas Th2 interleucina (IL)‐4 e IL‐13, estudios recientes han demostrado la participación de linfopoyetina del estroma tímico, IL‐5 e IL‐31 en la patogenia de la CH. La importancia de IL‐5 e IL‐31 se ha confirmado disminuir estas citoquinas mediante la inmunización activa de pacientes con CH, lo que da como resultado una mejora significativa de las puntuaciones de lesiones de CH. Treinta alérgenos salivales de Culicoides se han descrito en los últimos 10 años y se han producido como proteínas recombinantes puras (r‐). El uso de un microarray de proteínas ha permitido la identificación de los r‐alérgenos de Culicoides más relevantes para la CH en el centro y norte de Europa. Se ha desarrollado un protocolo de inmunización para la AIT preventiva contra la CH. Pequeñas cantidades de alérgenos de r‐Culicoides inyectados en los ganglios linfáticos submandibulares con Alum /MPLA como adyuvantes parecen inducir una respuesta inmune adecuada tanto para la AIT preventiva como para la terapéutica. Los próximos años revelarán si estos avances recientes se traducirán en un mejor diagnóstico, tratamiento y prevención de la CH.